HERMETO: A NL Analysis Environment - Martins, Ronaldo Teixeira; Hasegawa, Ricardo; Nunes, Maria das Graças Volpe (Proceedings of the Brazilian Symposium in Information and Human Language Technology (STIL); 2004: Proceedings of the 2nd Workshop in Information and Human Language Technology, 2004)
This paper describes HERMETO, a computational environment for fully-automatic, both syntactic and semantic, natural language analysis and understanding. HERMETO converts lists into networks and has been used to enconvert Brazilian Portuguese and English sentences into Universal Networking Language (UNL) hypergraphs.